Portable magnetic tweezers device enables visualization of the three-dimensional microscale deformation of soft biological materials. (July 2011) - Yang, Yali; Lin, Jun; Meschewski, Ryan; Watson, Erin; Valentine, Megan T.
We have designed and built a magnetic tweezers device that enables the application of calibrated stresses to soft materials while simultaneously measuring their microscale deformation using confocal microscopy. Unlike previous magnetic tweezers designs, our device is entirely portable, allowing easy use on microscopes in core imaging facilities or in collaborators' laboratories. The imaging capabilities of the microscope are unimpaired, enabling the 3-D structures of fluorescently labeled materials to be precisely determined under applied load. With this device, we can apply a large range of forces (∼1–1200 pN) over micron-scale contact areas to beads that are either embedded within 3-D matrices or attached to the surface of thin slab gels. To demonstrate the usefulness of this instrument, we have studied two important and biologically relevant materials: polyacrylamide-based hydrogel films typical of those used in cell traction force microscopy, and reconstituted networks of microtubules, essential cytoskeletal filaments.